Compartmentalized regulation of macrophage arachidonic acid metabolism (The Rockefeller University Press, 1986)
We show that downregulation of arachidonic acid (20:4) metabolism which occurs following i.p. injection of C. parvum can occur in a single, localized macrophage population, and is therefore unlikely to be mediated solely by a systemic factor.